2010
DOI: 10.1371/journal.pone.0012146
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Swimming Velocity Predicts Competitive Fertilization Success in the Green Swordtail Xiphophorus helleri

Abstract: Sperm competition is expected to favour the evolution of traits that influence the performance of sperm when they compete to fertilize a female's eggs. While there is considerable evidence that selection favours increases in sperm numbers, much less is known about how sperm quality contributes towards competitive fertilization success. Here, we determine whether variation in sperm quality influences competitive fertilization success in the green swordtail Xiphophorus helleri, a highly promiscuous livebearing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 45 publications
(55 reference statements)
4
104
2
Order By: Relevance
“…Sperm velocity is an important determinant of sperm competition success in several external and internal fertilizers [30,31,60,61] and in our guppy population [62], and it is influenced by its interaction with female OF [26,63]. We first demonstrated that the guppy OF positively affects sperm velocity.…”
Section: Discussionmentioning
confidence: 85%
“…Sperm velocity is an important determinant of sperm competition success in several external and internal fertilizers [30,31,60,61] and in our guppy population [62], and it is influenced by its interaction with female OF [26,63]. We first demonstrated that the guppy OF positively affects sperm velocity.…”
Section: Discussionmentioning
confidence: 85%
“…One-way analysis of variance (ANOVA) was used 186 to analyze data with normal distribution. Significant differences were detected using theusing the statistical package SPSS version 19 …”
Section: Statistical Analysis 183mentioning
confidence: 99%
“…Because the first spermatozoon to reach the ovum is more likely to engage in fertilisation (Cummins & Yanagimachi 1982), faster swimming speed is regarded as an adaptive trait. Sperm swimming velocity has been shown to be an important determinant of fertilisation success under both competitive (Birkhead et al 1999, Gage et al 2004, Gasparini et al 2010) and non-competitive scenarios , Levitan 2000, Malo et al 2005.…”
Section: Introductionmentioning
confidence: 99%